Advancements in materials, manufacturing, propulsion and localization: propelling soft robotics for medical applications - Bo, Yunwen; Wang, Haochen; Niu, Hui; He, Xinyang; Xue, Quhao; Li, Zexi; Yang, Hao; Niu, Fuzhou (Frontiers in Bioengineering and Biotechnology, 2024)
Soft robotics is an emerging field showing immense potential for biomedical applications. This review summarizes recent advancements in soft robotics for in vitro and in vivo medical contexts. Their inherent flexibility, adaptability, and biocompatibility enable diverse capabilities from surgical assistance to minimally invasive diagnosis and therapy. Intelligent stimuli-responsive materials and bioinspired designs are enhancing functionality while improving biocompatibility. Additive manufacturing techniques facilitate rapid prototyping and customization. Untethered chemical, biological, and wireless propulsion methods are overcoming previous constraints to access new sites. Meanwhile, advances in tracking modalities like computed tomography, fluorescence and ultrasound imaging enable precision localization and control enable in vivo applications. While still maturing, soft robotics promises more intelligent, less invasive technologies to improve patient care. Continuing research into biocompatibility, power supplies, biomimetics, and seamless localization will help translate soft robots into widespread clinical practice.